INFLUENCE OF TRANSPARENCY AND RELATIONSHIP ON SOUTH SULAWESI SMES’ COMPLIANCE - Nurfadilah, Nurfadilah; Ega Susanto, Setya; Harianti, Harianti; Ali Karim, Muhammad (Penerbit Lafadz Jaya, 2026)
Small and Medium Enterprises (SMEs) as the backbone of the national economy face significant challenges in terms of tax compliance. This study aims to understand the effect of taxpayer transparency and the quality of working relationships with tax authorities on SME tax compliance in South Sulawesi. The method used is a quantitative approach through distributing questionnaires and path analysis using SMART-PLS. The results showed that the quality of working relationships had a significant effect on tax compliance, both directly and through the mediation of taxpayer transparency. Transparency is also proven to have a strong influence on increasing compliance. This confirms the importance of harmonious relationships and information disclosure between taxpayers and tax authorities. The implications of these findings can be used by tax authorities to design policies that encourage compliance, particularly through improving relationship quality and transparency. In addition to practical contributions, this study also enriches the literature on tax compliance behavior in the SME sector and serves as a reference in evidence-based decision making in the field of taxation.